Gut Microbiota in Patients with Type 1 Narcolepsy - Zhang R; Gao S; Wang S; Zhang J; Bai Y; He S; Zhao P; Zhang H (Nature and Science of Sleep, 2021)
Ruirui Zhang,1 Shanjun Gao,2 Shenghui Wang,3 Jiewen Zhang,1,3 Yingying Bai,3 Shuang He,3 Pan Zhao,3 Hongju Zhang1,3 1Department of Neurology, Henan Provincial People’s Hospital Affiliated to Henan University, Zhengzhou, Henan, People’s Republic of China; 2Microbiome Laboratory, Henan Provincial People’s Hospital, Zhengzhou, Henan, People’s Republic of China; 3Department of Neurology, Henan Provincial People’s Hospital Affiliated to Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Hongju ZhangDepartment of Neurology, Henan Provincial People’s Hospital Affiliated to Henan University, Zhengzhou, Henan, People’s Republic of ChinaEmail hongjuz@sina.comPurpose: To explore the characteristics of gut microbiota and its relationship between clinical manifestations in patients with type 1 narcolepsy (NT1).Patients and Methods: Scale and polysomnography were performed in 20 NT1 patients and 16 healthy controls (HC group) to evaluate the clinical characteristics of NT1. Illumina sequencing was performed on bacterial 16S ribosomal RNA gene using V3-V4 regions to compare the fecal microbiota in all subjects. Associations between clinical characteristics and gut microbiota were analyzed using partial correlation analysis.Results: Compared with the HC group, the NT1 group had a significantly higher ESS score, longer total sleep time, increased wakefulness, decreased sleep efficiency, disturbance of sleep structure, shorter mean sleep latency, and increased sleep-onset REM periods (all P < 0.05). No differences in alpha and beta diversity were observed between the two groups. In contrast, there were significant differences at the level of class, order, family, and genus (all P < 0.05). LEfSe analysis showed that the relative abundance of Klebsiella in the NT1 group was higher than that in the HC group (P < 0.05), while the relative abundance of Blautia, Barnesiellaceae, Barnesiella, Phocea, Lactococcus, Coriobacteriia, Coriobacteriales, Ruminiclostridium_5, and Bilophila were lower (all P < 0.05). Partial correlation analysis revealed that partial differential bacteria in the NT1 group were correlated with total sleep time, sleep efficiency, stage 1 sleep, arousal index, and sleep latency (all P < 0.05).Conclusion: Our data revealed differences in intestinal flora structure between NT1 patients and the normal population, thus providing a theoretical basis for future microecological therapy for narcolepsy. However, future larger sample size studies and different study designs are needed to further clarify the possible pathogenesis and potential causality of intestinal flora in NT1 patients and explore the new treatment strategies.Keywords: type 1 narcolepsy, gut microbiota, 16SrRNA, high throughput sequencing